INDEPENDENT INSTITUTIONS AS INSTRUMENTS OF CHECKS AND BALANCES IN THE BRAZILIAN STATE - do Nascimento, Mário Oli; Gomes, Myke Oliveira; Souza, Wagner Fonseca (Seven Editora, 2026)
Independent institutions constitute fundamental pillars of the democratic rule of law, performing functions of oversight, supervision, and balance among powers. In Brazil, Courts of Accounts, the Public Prosecutor’s Office, the Public Defender’s Office, and regulatory agencies exemplify institutions that materialize the system of checks and balances. This study analyzes independent institutions as instruments of checks and balances in the Brazilian State, examining their functions, autonomy, and effectiveness. The methodology is characterized as an exploratory bibliographic review with a qualitative approach, grounded in the critical analysis of scientific publications from 2020 to 2025. The results indicate that independent institutions perform essential functions of control and rights protection, but face challenges related to autonomy, legitimacy, and coordination. Institutional effectiveness depends on adequate resources, technical capacity, and inter-organizational articulation. It is concluded that independent institutions are fundamental components of the democratic institutional architecture and require protection and strengthening, balancing autonomy and accountability to ensure effective democratic governance. DOI: https://doi.org/10.56238/sevened2026.008-088